1991
DOI: 10.1016/0304-3959(91)90157-s
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of desipramine in painful diabetic neuropathy: a placebo-controlled trial

Abstract: Although amitriptyline relieves pain in many patients with painful diabetic neuropathy, side effects often preclude effective treatment. Desipramine has the least anticholinergic and sedative effects of the first generation tricyclic antidepressants. We compared a 6 week course of desipramine (mean dose, 201 mg/day) to active placebo in 20 patients with painful diabetic neuropathy in a double-blind crossover trial. Pain relief with desipramine was statistically significant in weeks 5 and 6. Eleven patients rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
0
7

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(128 citation statements)
references
References 28 publications
3
118
0
7
Order By: Relevance
“…20, [40][41][42] Several studies have documented that the analgesic effect is independent of the antidepressant effect and that these agents are effective in patients with persistent pain who do not have concurrent depression. [43][44][45] Also it has been observed that analgesic action is strongest in antidepressants with mixedreceptor or predominantly noradrenergic activity. 46,47 …”
Section: Antidepressants As Analgesicsmentioning
confidence: 99%
“…20, [40][41][42] Several studies have documented that the analgesic effect is independent of the antidepressant effect and that these agents are effective in patients with persistent pain who do not have concurrent depression. [43][44][45] Also it has been observed that analgesic action is strongest in antidepressants with mixedreceptor or predominantly noradrenergic activity. 46,47 …”
Section: Antidepressants As Analgesicsmentioning
confidence: 99%
“…Examples include efficacy of alleviating neuropathic pain behavior in rat models of DPN using tricyclic antidepressants [52,53,55,56] and morphine [55]. Clinical trials demonstrating efficacy with tricyclic antidepressants [57][58][59][60][61] and opioids [62,63] provide further validation of the usefulness of these outcome measures.…”
Section: Diabetic Neuropathymentioning
confidence: 99%
“…10 Tricyclic antidepressants (TCAs) with reuptake inhibitory activity for both 5-HT and NE have been widely used in the management of DPNP. 11,12 Hypothetically, dual reuptake inhibitors unburdened by the undesirable pharmacologic effects of TCAs should be better tolerated and more effective in managing diabetic peripheral neuropathic pain (DPNP). This hypothesis is supported by the finding that amitriptyline (5-HT and NE reuptake inhibitor) is superior to desipramine (NE reuptake inhibitor), which is superior to fluvoxamine (5-HT reuptake inhibitor) in providing pain relief.…”
Section: Introduction Dmentioning
confidence: 99%